Hypnobreastfeeding dan Motivasi Pemberian ASI - Asih, Yusari (Politeknik Kesehatan Tanjung Karang, 2020)
Breastmilk is the only perfect and best food for babies because it contains the nutritional elements needed by babies for optimal growth and development. Although the rate of exclusive breastfeeding in the Pringsewu Regency has increased from year to year, support for community participation and empowerment in health development has not been optimal. One solution that can help overcome barriers to exclusive breastfeeding is hypnobreastfeeding. The purpose of this study was to determine the effect of hypnobreastfeeding on the motivation of breastfeeding in the Pringsewu Regency in 2019. This research is a quasi-experimental research with pre-post-test design with a control group design. The sampling technique was purposive sampling with a sample size of 48 pregnant women from term to breastfeeding. Data analysis was done by using the Independent Two Mean Difference test (T-Test) using the Paired Sample Test. The results of the study on the Paired Sample Test showed a significant value (p) of 0.004, meaning that there was a significant difference in the motivation of breastfeeding before and after hypnobreastfeeding. Midwives always provide hypnobreastfeeding therapy and lactation education to help increase motivation for breastfeeding as part of efforts to increase exclusive breastfeeding and breastfeeding for up to 2 years or more. For other researchers, it is necessary to carry out further research with other variables that can affect the motivation of breastfeeding.